METHODS OF IMPROVING AND DEVELOPING READING SKILLS - Rustamova, Shahnoza; Turg`unova Fazilat Rustam qizi, (Журнал иностранных языков и лингвистики, 2023)
In our article, the development of professional competence of prospective teachers during their studies is facilitated by providing the following psychological and pedagogical conditions: Sometimes examples are considered and analyzed why reading is important. Reading is important for several reasons. Check out some of these key reasons below, but it's important to understand that struggling with basic literacy skills doesn't equate to low intelligence.